Unwarranted intrusions : - Fridson, Martin S. (J. Wiley, 2006)
What happens when politicians substitute their wisdom for the market’s? The result is usually a government subsidy that provides advantage to a special interest group only–but costs everyone and drains the economy. In Unwarranted Intrusions, well-known financial commentator Martin Fridson turns his sharp eye for uncovering opaque financial reporting practices to the U.S. government and examines the economic reality of some of the most popular yet financially draining subsidies. Fridson debunks programs that claim to provide jobs, encourage savings, provide affordable housing, and preserve family farms–among many others. Unwarranted Intrusions is a provocative and exhaustively researched challenge to prevailing political claims of programs that purport to protect the public good.